Modulation of the intestinal bile acid/farnesoid X receptor/fibroblast growth factor 15 axis improves alcoholic liver disease in mice. Issue 6 (16th April 2018) - Hartmann, Phillipp; Hochrath, Katrin; Horvath, Angela; Chen, Peng; Seebauer, Caroline T.; Llorente, Cristina; Wang, Lirui; Alnouti, Yazen; Fouts, Derrick E.; Stärkel, Peter; Loomba, Rohit; Coulter, Sally; et al.
Abstract : Alcoholic liver disease (ALD) is associated with changes in the intestinal microbiota. Functional consequences of alcohol‐associated dysbiosis are largely unknown. The aim of this study was to identify a mechanism of how changes in the intestinal microbiota contribute to ALD. Metagenomic sequencing of intestinal contents demonstrated that chronic ethanol feeding in mice is associated with an over‐representation of bacterial genomic DNA encoding choloylglycine hydrolase, which deconjugates bile acids in the intestine. Bile acid analysis confirmed an increased amount of unconjugated bile acids in the small intestine after ethanol administration. Mediated by a lower farnesoid X receptor (FXR) activity in enterocytes, lower fibroblast growth factor (FGF)‐15 protein secretion was associated with increased hepatic cytochrome P450 enzyme (Cyp)‐7a1 protein expression and circulating bile acid levels. Depletion of the commensal microbiota with nonabsorbable antibiotics attenuated hepatic Cyp7a1 expression and reduced ALD in mice, suggesting that increased bile acid synthesis is dependent on gut bacteria. To restore intestinal FXR activity, we used a pharmacological intervention with the intestine‐restricted FXR agonist fexaramine, which protected mice from ethanol‐induced liver injury. Whereas bile acid metabolism was only minimally altered, fexaramine treatment stabilized the gut barrier and significantly modulated hepatic genes involved in lipid metabolism. To link the beneficial metabolic effect to FGF15, a nontumorigenic FGF19 variant—a human FGF15 ortholog—was overexpressed in mice using adeno‐associated viruses. FGF19 treatment showed similarly beneficial metabolic effects and ameliorated alcoholic steatohepatitis. Conclusion: Taken together, alcohol‐associated metagenomic changes result in alterations of bile acid profiles. Targeted interventions improve bile acid–FXR–FGF15 signaling by modulation of hepatic Cyp7a1 and lipid metabolism, and reduce ethanol‐induced liver disease in mice. (Hepatology 2018;67:2150‐2166).